Unexpected Hole Doping of Graphene by Osmium Adatoms. Issue 2 (6th November 2019) - Elias, Jamie A.; Henriksen, Erik A.
Abstract: The electronic transport of monolayer graphene devices is studied before and after in situ deposition of a sub‐monolayer coating of osmium adatoms. Unexpectedly, and unlike all other metallic adatoms studied to date, osmium adatoms shift the charge neutrality point to more positive gate voltages. This indicates that osmium adatoms act as electron acceptors and thus leave the graphene hole‐doped. Analysis of transport data suggest that Os adatoms behave as charged impurity scatterers, albeit with a surprisingly low charge‐doping efficiency. The charge neutrality point of graphene is found to vary non‐monotonically with gate voltage as the sample is warmed to room temperature, suggesting that osmium diffuses on the surface but is not completely removed. Abstract : Dilute coatings of transition metal adatoms may be a path toward inducing a non‐trivial spin–orbit coupling in graphene. Here, electronic transport measurements on osmium‐decorated graphene find that Os adatoms donate holes into graphene rather than electrons as expected.